Conserved age‐related increases in hippocampal PDE11A4 cause unexpected proteinopathies and cognitive decline of social associative memories. Issue 10 (8th September 2022) - Pilarzyk, Katy; Porcher, Latarsha; Capell, William R.; Burbano, Steven D.; Davis, Jeff; Fisher, Janet L.; Gorny, Nicole; Petrolle, Siena; Kelly, Michy P.
Abstract: In humans, associative memories are more susceptible to age‐related cognitive decline (ARCD) than are recognition memories. Reduced cAMP/cGMP signaling in the hippocampus may contribute to ARCD. Here, we found that both aging and traumatic brain injury‐associated dementia increased the expression of the cAMP/cGMP‐degrading enzyme phosphodiesterase 11A (PDE11A) in the human hippocampus. Further, age‐related increases in hippocampal PDE11A4 mRNA and protein were conserved in mice, as was the increased vulnerability of associative versus recognition memories to ARCD. Interestingly, mouse PDE11A4 protein in the aged ventral hippocampus (VHIPP) ectopically accumulated in the membrane fraction and filamentous structures we term "ghost axons." These age‐related increases in expression were driven by reduced exoribonuclease‐mediated degradation of PDE11A mRNA and increased PDE11A4‐pS117/pS124, the latter of which also drove the punctate accumulation of PDE11A4. In contrast, PDE11A4‐pS162 caused dispersal. Importantly, preventing age‐related increases in PDE11 expression via genetic deletion protected mice from ARCD of short‐term and remote long‐term associative memory (aLTM) in the social transmission of food preference assay, albeit at the expense of recent aLTM. Further, mimicking age‐related overexpression of PDE11A4 in CA1 of old KO mice caused aging‐like impairments in CREB function and remote social—but not non‐social—LTMs. RNA sequencing and phosphoproteomic analyses of VHIPP identified cGMP‐PKG—as opposed to cAMP‐PKA—as well as circadian entrainment, glutamatergic/cholinergic synapses, calcium signaling, oxytocin, and retrograde endocannabinoid signaling as mechanisms by which PDE11A deletion protects against ARCD. Together, these data suggest that PDE11A4 proteinopathies acutely impair signaling in the aged brain and contribute to ARCD of social memories. Abstract : We identify striking ectopic proteinopathies in the hippocampally‐enriched cAMP/cGMP‐degrading enzyme PDE11A4 as a conserved molecular determinant driving age‐related cognitive decline (ARCD) of associative long‐term memories. Mechanistically, these age‐related PDE11A4 proteinopathies are driven by increased translation and altered trafficking triggered by phosphorylation of serines S117 and S124 in the PDE11A4 regulatory domain. RNA and phosphoproteomic analyses identified cGMP‐PKG (as opposed to cAMP‐PKA), circadian entrainment, glutamate/choline, calcium, oxytocin, and retrograde endocannabinoid signaling as pathways by which PDE11A deletion protects against ARCD.